2017
DOI: 10.1016/j.fertnstert.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation treatments—where is the evidence?

Abstract: While advances in assisted reproductive techniques have been substantial, failure of the apparently viable embryo to implant remains a source of distress and frustration to patients and specialists alike. The unique maternal immunological response to the embryo and the notion that defects in early placentation underlie the great complications of pregnancy have focused attention on the therapeutic potential of peri-implantation immunomodulation. On the face of it, the rationale for this approach is very attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 59 publications
2
32
2
2
Order By: Relevance
“…3b). This is in agreement with previous findings in human that reproduction traits have been linked with immunological processes such as allergic response to sperm and immunological tolerance of the embryo [39]. We observed that mammary is the top significant tissue for somatic cell score (SCS, an indicator of mastitis), consistent with prior knowledge that an infection of the udder is the main cause for increased somatic cell counts in milk [40].…”
Section: Trait-relevant Tissuessupporting
confidence: 93%
“…3b). This is in agreement with previous findings in human that reproduction traits have been linked with immunological processes such as allergic response to sperm and immunological tolerance of the embryo [39]. We observed that mammary is the top significant tissue for somatic cell score (SCS, an indicator of mastitis), consistent with prior knowledge that an infection of the udder is the main cause for increased somatic cell counts in milk [40].…”
Section: Trait-relevant Tissuessupporting
confidence: 93%
“…Immunotherapy for implantation failure or miscarriage is a controversial strategy, with a lack of strong evidence to support its routine use [45]. A common theme to many of these investigations is poor study design and patient selection which perhaps underpowers the work to show a significant impact of therapy on outcomes such as live birth [46] or adds potential bias during patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to determine the relative effect of each component would allow a more personalised protocol for each individual patient. Studies assessing the individual relative benefits of the empiric treatments described here have previously been conducted with variable findings both advocating and not advocating their use [ 21 , 48 , 49 ]. The success of the regimen employed here as evidenced by improved implantation, successful pregnancies and a dramatic reduction in the overall miscarriage rate demonstrates both the combined beneficial effect of these agents as well as the potential importance of specific immunological testing in selected cases.…”
Section: Discussionmentioning
confidence: 99%